Value of liver biopsy in anorexia nervosa‐related transaminitis: A case study and literature review. Issue 7 (1st June 2022) - Faragalla, Kyrillos; So, Jeffrey; Chan, Pak C.; Wang, Hanlin L.; Liu, Jimin
Abstract: Anorexia nervosa (AN) is a complex eating disorder that affects multiple organs. 60% of patients have liver injury with transaminitis. The mechanism of liver injury in AN remains unclear. We present a case of a 19‐year‐old female with AN was admitted to our hospital with marked transaminitis but near normal liver histology on biopsy. Her transaminitis eventually improved as she regained weight. We also conducted a literature review of similar cases to delineate the clinicopathologic spectrum of liver injury in AN patients. English published cases of adult AN patients with elevated transaminases who underwent a liver biopsy or autopsy were selected. 32 cases (including ours). All except four patients were female, with median age of 26.5 years and median body mass index 11.9 kg/m 2 . Presentations mainly included hypoglycemic coma and weight loss. 63% of patients had severe transaminitis (AST >15x ULN). Other lab findings included elevated international normalized ratio (72%) and hypoalbuminemia (47%). Microscopically, all cases showed intact hepatic architecture. Fibrosis was reported in 12 cases and necroinflamfmation in 8, but only half of each had severe transaminitis. AN patients display a wide spectrum of liver histopathology which often does not correlate with the degree of transaminitis. In severe persistent AN‐related transaminitis, liver biopsy is useful to assess the degree of liver injury and to exclude other potential etiologies.